La defectuosa construcción del lawfare como mito en Brasil y Argentina: entre la pesadilla y el noble sueño de la neutralidad política en la justicia penal - Laise, Luciano D. (Pontificia Universidad Católica del Perú, 2023)
The notoriety that criminal proceedings against Latin-American political figures have acquired led some to argue that such proceedings constitute a perverse attack against popular leaders who oppose the neoliberal agendas of the global north. Before this issue, in this article I intend to systematically reconstruct the specialized literature on the concept of lawfare. Then I will outline both mythical and fallacious nature of many of the explanations and implications for so-called lawfare. Since those criticisms, I will highlight two relevant topics: (i) the necessary respect for the basic procedural guarantees for any person who is accused of serious crimes against public administration, and (ii) the inevitable political dimension of legal interpretation.

La notoriedad que han adquirido los procesos penales contra personajes de la política hispanoparlante ha llevado a algunos a sostener que estamos ante un embate perverso contra líderes populares que se oponen a las agendas neoliberales del norte global. Frente a tal asunto, en este artículo pretendo reconstruir de manera sistemática la literatura especializada sobre el concepto de lawfare. Luego, esbozaré la naturaleza tanto mítica como falaciosa de muchas de las explicaciones e implicaciones sobre el llamado lawfare. A partir de esto se advertirán dos cuestiones relevantes: (i) el necesario respeto de las garantías procesales básicas para toda persona que resulta acusada de graves delitos de corrupción, y (ii) la inevitable dimensión política de la interpretación jurídica.
Constructing a Defective Myth: The Case of Lawfare Between Nightmare and a Noble Dream of Neutral Politics in Criminal Courts
Keywords: Corruption; Hybrid war; Political myth; Legal argumentation; Right to due process; Lawfare; Corrupción; Guerra híbrida; Mito político; Argumentación jurídica; Derecho al debido proceso; Lawfare; https://purl.org/pe-repo/ocde/ford#5.05.00